Paget’s Disease of the Vulva in Premenopausal Woman Treated with Only Surgery: A Case Report - Hamid Asmouki; Rachid Oumouloud; Abderrahim Aboulfalah; Abderraouf Soummani; Abdelouahed Marrat (Case Reports in Oncological Medicine)
Paget’s disease of the vulva remains a rare condition with only a limited number of cases reported in the literature. It is an uncommon neoplasm usually of postmenopausal white women characterized by controversies in its prevalence, clinical features, treatment strategies, and prognostic. We here report a case of a primary Paget’s disease of the vulva in premenopausal woman treated by only surgery with a favorable issue.